A case study in controlled source electromagnetism: Near seabed hydrocarbon seep systems of Coal Oil Point, California, USA. (May 2022) - King, Roslynn B.; Constable, Steven; Maloney, Jillian M.
Abstract: Marine hydrocarbon seeps are found on all continental margins and release significant amounts of greenhouse gases and hydrocarbons into the atmosphere and hydrosphere. Most methods of studying seeps rely on seafloor or near-seafloor observations, but seepage rates and seep locations can be variable, leading to uncertainty. We exploit the fact that hydrocarbons are electrically resistive compared with surrounding sediments and use marine electromagnetic methods to study the deeper sources and accumulation sites, which are controlled by local geology and should be more stable than the seabed expressions. Our surface towed marine controlled source electromagnetic system used a horizontal electric dipole transmitter and floating electric dipole receivers spaced 100–400 m from the transmitter, collecting frequency domain amplitude and phase data at ∼2 Hz and harmonics. The survey targeted known and inferred hydrocarbon seeps within the Coal Oil Point seep field offshore Santa Barbara, California, USA. Two dimensional inversions of the data indicate that the method is sensitive to the shallowly buried (<400 m) structure of the marine hydrocarbon seeps and is an efficient and effective tool in their identification and characterization. The results show spatial variability of seafloor hydrocarbons along the Coal Oil Point seep field and indicate at least two previously unidentified intermediate depth accumulation sites. The depth and lateral extent of these hydrocarbon accumulation sites may improve seep emission models for the Coal Oil Point seep field. Highlights: Marine EM sounding is an effective and efficient tool to study marine hydrocarbon seep geology. Two previously unidentified hydrocarbon accumulation sites associated with overlying marine hydrocarbon seeps were imaged. Resistivity models indicate significant changes in seafloor spatial extent of the Patch Seep compared to recent observations. Vertical resistive features are collocated with faults and fractures indicating potential hydrocarbon migration pathways.